Melibea Lies - Connie L. Scarborough (Celestinesca, 2021)
A close rereading of the Tragicomedia de Calisto y Melibea reveals a singularly striking element of Melibea’s personality –she is a habitual liar. She lies to Calisto, she lies to Celestina, she lies to her mother, she lies to her maid Lucrecia, she lies to her father, and most decisively, she lies to herself. While we might label the latter a mere case of self-deception or self-justification, her consistent proclivity to lie is at the center of her personality. Melibea exercises free will throughout the work. She decides to lie, to stray from the paths of truth, common sense, and realistic consideration of the consequences of her decisions. This fundamental trait of her personality contributes to the tragedia embedded in the hybrid title of the Tragicomedia.